1999
DOI: 10.1080/00071669987034
|View full text |Cite
|
Sign up to set email alerts
|

Composition of vitamin supplements in Spanish poultry diets

Abstract: 1. The composition of 106 vitamin supplements used in about 85% of the Spanish poultry production diets were studied. Vitamin supplements were grouped by production classes and, for broilers and pullets, also by feeding periods. 2. Four vitamins (niacin, alpha-tocopherol, pantothenic acid, and riboflavin) comprised over 87% of the vitamin supplements by weight (choline excluded), whereas alpha-tocopherol and retinol represented from 51% to 60% of the total vitamin cost. 3. The highest and lowest vitamin supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The British and French producers we contacted also indicated that they follow the FEFANA guidelines. A 20-year-old Spanish survey on vitamins in chicken feed [94] showed measured vitamin concentrations, which match well with current FEFANA regulations regarding B-Vitamins, but are clearly lower regarding vitamin E. The latter shows that, due to increasing performance and thus metabolic rates of animals, the feed producers currently add high safety margins. As long as no specific data and recommendations for vitamin supplements to organic livestock exist, there is no reason to use different supplementation levels for the organic sector.…”
Section: Current Use Of Vitamins and Its Alternatives In Organic Live...supporting
confidence: 59%
See 1 more Smart Citation
“…The British and French producers we contacted also indicated that they follow the FEFANA guidelines. A 20-year-old Spanish survey on vitamins in chicken feed [94] showed measured vitamin concentrations, which match well with current FEFANA regulations regarding B-Vitamins, but are clearly lower regarding vitamin E. The latter shows that, due to increasing performance and thus metabolic rates of animals, the feed producers currently add high safety margins. As long as no specific data and recommendations for vitamin supplements to organic livestock exist, there is no reason to use different supplementation levels for the organic sector.…”
Section: Current Use Of Vitamins and Its Alternatives In Organic Live...supporting
confidence: 59%
“…Proportion of allowed amount used by organic farms (%) 94 As for estimating the copper use in different crop categories in the 12 countries, the report concluded that olive and grape production accounts for the majority (69%) of the total copper use. Figure 1 summarizes the total estimated copper use/year in the 12 countries in different crop categories.…”
Section: Current Use Of Copper and Its Alternatives In Organic Crop P...mentioning
confidence: 99%
“…These studies are often conducted under highly controlled, low-stress conditions, using purified or semi-purified diets that are not reflective of commercial conditions. A survey of 25 commercial Spanish vitamin premix manufacturers showed that safety margins (relative to NRC, 1994 ) for supplemental vitamins in broiler diets ranged from 2.1- to 13.7-fold for fat-soluble vitamins, and 0.5- to 2.1-fold for water-soluble vitamins excluding choline ( Villamide and Fraga, 1999 ). The supplementation rates below the NRC (1994) requirement for some vitamins represent the vitamin contributions provided by the other dietary ingredients such as cereal grains and oilseed meals.…”
Section: Changes In Nutrient Requirements With Genetic Selection For ...mentioning
confidence: 99%